METODE KOMUNIKASI BAGI ANAK BERKEBUTUHAN KHUSUS - Gina Gantini Evarahma (Jurnal Bimbingan Penyuluhan Islam, 2022)
The need for each individual to communicate is a manifestation of the existence of the individual as a social being. A person's ability to communicate is an absolute necessity that must be met in their efforts to self-actualize. This communication ability applies universally to every individual in their need to survive. Communication problems often occur in those who have developmental barriers both physically and psychologically in communicating. These obstacles also often occur in children in the group of children with special needs (ABK). Children with special needs are children who in the process of growth or development experience abnormalities or deviations (physical, mental, intellectual, social, emotional), so they require special treatment. Some forms of developmental barriers and deviations in children with special needs as often known as blind, deaf, mentally retarded, physically handicapped, slow learners, gifted, mentally retarded, ADHD, and autism. The diversity of developmental characters and the obstacles they experience will lead to different communication models that we can present for them in helping them to carry out social interactions. The effectiveness of communication that occurs with them is very dependent on the instruments they use to assist them in communicating with all their limitations.